Fragmented and Polarised? The German Public Sphere during the Russian Invasion of Ukraine - Conrad, Maximilian (Javnost-The Public, 2024)
The digital age has brought about fundamental questions about the viability of the public sphere. While a shared and inclusive communicative space is widely considered to be a fundamental requirement for democratic deliberation, the rise of social (and other digital) media has prompted concerns about a potential fragmentation of the public sphere. Accompanied by the simultaneous decline of quality journalism, social media have facilitated the emergence of semi-public echo chambers of like-minded people. Against the backdrop of debates on post-truth politics, such echo chambers are important arenas for the dissemination of false information, but they also undermine the epistemic added value of deliberation by inhibiting discussion on competing truth claims. Based on the argument that post-truth politics is intimately connected to the fragmentation of the public sphere, this article analyses the extent to which the German public sphere has shown signs of polarisation and fragmentation in the context of the Russian invasion of Ukraine in early 2022. This is done by investigating to which extent to which debates in leading German media have managed to adequately represent all relevant perspectives on the Russian invasion, and conversely to which extent dissonant voices have been excluded from such debates.